Investigation into Some Aspects of Partial Ductile Mode in Wet and Dry Grinding of optical Glass - Sudin, I. (2004)
Machining of hard and brittle materials always pose problems such as rough surface, cracks, subsurface damage and residual stresses mainly due to its brittle nature. Recent developments in cutting tool technology coupled with rigid ultraprecision machine tools have made it possible to machine hard and brittle materials like optical glass in ductile mode with crack free surfaces. However this technique is reported to be relatively slow and too expensive for manufacturing less precision products like ophthalmic lenses, which do not require extreme form accuracy. Though not possible to machine glass in fully ductile mode with conventional grinding, substantial amount of partial ductile mode areas generated on the ground surface is proven to reduce polishing time significantly to get mirror finish. In this study, resinoid bonded diamond pins, with and without a central hole were used to grind BK7 optical glass. Plano grinding operation was carried out using a high-speed jig grinder air motor, which was attached to a vertical spindle CNC milling machine. Both wet and dry grinding operations were performed. In wet grinding, ductile-fracture areas and surface roughness of ground surface were investigated by varying grinding conditions. Diamond grinding pins with and without central hole were found to have an effect on surface finish and flatness on the ground surfaces. Central holed diamond pins produced better surface finish and were 5 times superior in flatness compared to surfaces ground with diamond pins without central hole. Subsequently, zero velocity effect that cause chips trapped underneath of diamond pins are completely eliminated. Insufficient coolant penetration into grinding zone and fixture rigidity were found to have contributed stalling marks. Applications of higher coolant flow rate of 5 litres/min together with a rigid pocket groove holder were successfully used to eliminate stalling and this set-up was used in subsequent experimental trials for ductile-fracture and surface roughness analysis. Maximum ductile streaks were obtained at the lowest feed (5mm/min) and in-feed (5µm) for both 64µm and 126µm grit diamond pins. Finer ductile streaks were observed with 64µm than 126µm grit diamond pins in almost all conditions probably due to grain size effects. An image processing procedure has been successfully developed to quantify objectively the fraction of ductile and fracture areas generated on ground surfaces. Among the four alternatives developed, method B provided the least error. A linear relationship model was established for surface roughness when grinding with 64µm grit diamond pins. The feed was found to have significant effect on the response investigated. The model was verified by the confirmation run and therefore can be used for prediction within the limits of the factors investigated. In dry grinding, various types of chips morphology were observed. A discovery was made during this study, namely the observation of solid spherical glass chips obtained at the lowest cutting condition (feed = 2.5mm/min and infeed = 5µm) and its formation mechanism is described.